MANAJEMEN LABA AKRUAL PENDEKATAN MODIFIED JONES MODEL PADA SUBSEKTOR FOOD & BEVERAGE TAHUN 2018-2022 - Yuliyani, Alfia; Rois, Muhammad; Rikawati (Jurnal Akuntansi Trisakti, 2024)
This research is motivated by the possibility of earnings management through the use of loopholes in the accrual basis, that can mislead investors and creditors in decision making, if earning management is influenced by manager’s opportunistic behavior. The purpose of this study is to measure and analyze the accrual earnings management pattern in the Food & Beverage Subsector listed on the IDX in 2018-2022 using the Modified Jones Model. This research uses quantitative methods with secondary data are financial statements. The sample in this study was 22 companies that according to purposive sampling for being registered in the Food & Beverage Subsector consecutively during 2018-2022. The results showed that accrual earnings management in the Food & Beverage Subsector decreased during 2018-2022 with earning management pattern from observation is income decreasing. Meanwhile, the pattern of earnings management per year is income decreasing during 2018-2020 and 2022, and income increasing in 2021. The highest income decreasing by Pratama Abadi Nusa Industri Tbk. in 2018 was indicated by the highest negative discretionary accrual value and the highest income increasing were by the same company in 2021 was indicated by the highest positive discretionary accrual value.